Experimental Modeling Supports a Role for MyBP-HL as a Novel Myofilament Component in Arrhythmia and Dilated Cardiomyopathy. Issue 16 (17th October 2017) - Barefield, David Y.; Puckelwartz, Megan J.; Kim, Ellis Y.; Wilsbacher, Lisa D.; Vo, Andy H.; Waters, Emily A.; Earley, Judy U.; Hadhazy, Michele; Dellefave-Castillo, Lisa; Pesce, Lorenzo L.; McNally, Elizabeth M.
Abstract : Background: Cardiomyopathy and arrhythmias are under significant genetic influence. Here, we studied a family with dilated cardiomyopathy and associated conduction system disease in whom prior clinical cardiac gene panel testing was unrevealing. Methods: Whole-genome sequencing and induced pluripotent stem cells were used to examine a family with dilated cardiomyopathy and atrial and ventricular arrhythmias. We also characterized a mouse model with heterozygous and homozygous deletion of Mybphl . Results: Whole-genome sequencing identified a premature stop codon, R255X, in the MYBPHL gene encoding MyBP-HL (myosin-binding protein-H like), a novel member of the myosin-binding protein family. MYBPHL was found to have high atrial expression with low ventricular expression. We determined that MyBP-HL protein was myofilament associated in the atria, and truncated MyBP-HL protein failed to incorporate into the myofilament. Human cell modeling demonstrated reduced expression from the mutant MYBPHL allele. Echocardiography of Mybphl heterozygous and null mouse hearts exhibited a 36% reduction in fractional shortening and an increased diastolic ventricular chamber size. Atria weight normalized to total heart weight was significantly increased in Mybphl heterozygous and null mice. Using a reporter system, we detected robust expression of Mybphl in the atria, and in discrete puncta throughout the right ventricular wall and septum, as well. Telemetric electrocardiogram recordings in Mybphl mice revealed cardiac conduction system abnormalities with aberrant atrioventricular conduction and an increased rate of arrhythmia in heterozygous and null mice. Conclusions: The findings of reduced ventricular function and conduction system defects in Mybphl mice support that MYBPHL truncations may increase risk for human arrhythmias and cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.